2021
DOI: 10.1007/s12070-021-02581-1
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss-a Camouflaged Manifestation of COVID 19 Infection

Abstract: The symptomatology of novel Severe Acute Respiratory Syndrome Corona virus type 2 infection runs the entire gamut of mild to moderate and serious illness among the affected individuals. As listed in recent literature, respiratory, cardiovascular, gastrointestinal, olfactory and gustatory systems are commonly involved. With the growing knowledge about the disease, varied manifestations have been identified and lately, otorhinolaryngology dysfunctions in COVID 19 have been described. Hearing loss in COVID era is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Mustafa ( 2020 ) found that pure-tone hearing thresholds in high frequencies and amplitudes of transient evoked otoacoustic emissions (TEOAE) were significantly worse in this population, thus concluding that COVID-19 infection potentially has adverse effects on cochlear hair cell function even when infected individuals are asymptomatic for the cardinal disease symptoms. Similar findings were reported by Dharmarajan et al ( 2021 ), while Daher et al ( 2022 ) only found the hearing loss in the ultra-high frequencies, thus highlighting the need for inclusion of sensitive audiological measures such as ultra-high frequency audiometry and distortion product OAEs (DPOAEs).…”
Section: Resultssupporting
confidence: 81%
“…Mustafa ( 2020 ) found that pure-tone hearing thresholds in high frequencies and amplitudes of transient evoked otoacoustic emissions (TEOAE) were significantly worse in this population, thus concluding that COVID-19 infection potentially has adverse effects on cochlear hair cell function even when infected individuals are asymptomatic for the cardinal disease symptoms. Similar findings were reported by Dharmarajan et al ( 2021 ), while Daher et al ( 2022 ) only found the hearing loss in the ultra-high frequencies, thus highlighting the need for inclusion of sensitive audiological measures such as ultra-high frequency audiometry and distortion product OAEs (DPOAEs).…”
Section: Resultssupporting
confidence: 81%
“…Studies have highlighted the neurotropic and neuroinvasive nature of the COVID-19 virus (54), and the infection has been considered a plausible cause for hearing loss. Auditory symptoms, including hearing loss and tinnitus, are being frequently reported along with other usual symptoms in patients with COVID-19 (32,55,56). Being a neglected symptom, screening for hearing is being encouraged in the patients with COVID-19.…”
Section: Auditory Manifestationsmentioning
confidence: 99%
“…Middle ear pathologies can change the anatomical structure(s) of the middle ear system, particularly the tympanic membrane (Møller, 2013 ). In this review, three studies (Dharmarajan et al, 2021 ; Fidan et al, 2020 ; Wanna et al, 2020 ) have reported on the anatomical changes, particularly of the tympanic membranes, in patients infected with COVID-19. Fidan et al ( 2020 ) reported hyperaemia and bulging of the tympanic membrane, while in a case series by Dharmarajan et al ( 2021 ), four participants presented with retracted tympanic membrane and two had dull tympanic membranes.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, three studies (Dharmarajan et al, 2021 ; Fidan et al, 2020 ; Wanna et al, 2020 ) have reported on the anatomical changes, particularly of the tympanic membranes, in patients infected with COVID-19. Fidan et al ( 2020 ) reported hyperaemia and bulging of the tympanic membrane, while in a case series by Dharmarajan et al ( 2021 ), four participants presented with retracted tympanic membrane and two had dull tympanic membranes. While the third study (Wanna et al, 2020 ) did not specifically report on the anatomical structure of the tympanic membrane, this case study reported that a participant presented with purulent otorrhea, which may be indicative of tympanic membrane perforation (Ali & Alshareda, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation